Electronic Medical Record Systems: Decision Support Examination Framework for Individual, Security and Privacy Concerns Using Multi-perspective Analysis - Enaizan, O; Zaidan, AA; Zaidan, BB; Alsalem, MA; Albahri, OS; Albahri, AS; Najwa Hayaati Mohd Alwi (Springer Heidelberg, 2024)
Indexed by WOS/SCOPUS